Relevansi Informasi Laba, Nilai Buku Ekuitas, Arus Kas Operasi, dan Dividen Terhadap Harga Saham - Clarissa Serena Elargo; Carmel Meiden (LPPM POLITEKNIK LP3I BANDUNG, 2022)
In investment activities, investors need accounting information as a basis for making decisions. To be useful for decision making, the information must meet the relevant qualities seen from the reaction of the capital market through stock price movements. Since earnings is not the only indicator used to measure a company's financial performance, many studies have been conducted and developed to investigate new alternatives for measuring value relevance. Therefore, this study is interested in adding other information variables, namely operating cash flows and dividends. The manufacturing industry sector is an interesting sector to study because the manufacturing industry sector continues to grow and continues to increase from time to time. This study aims to determine the value relevance of accounting information on manufacturing companies listed on the IDX for the period 2011-2020. The object of this research is the annual financial statements of manufacturing companies listed on the Indonesia Stock Exchange for the period 2011-2020. Based on the purposive sampling method, a sample of 380 observations was obtained consisting of 38 companies per year. The data analysis techniques used in this research are pooling test, classical assumption test, descriptive statistical test, F test, t test and coefficient of determination test. The results of the tests carried out show that the data can be pooled. From the results of the t-test, each of the four accounting variables tested has a sig value below 0.05 with a positive sign coefficient. The Adjusted R2 value of earnings and book value of equity is 73% and the Adjusted R2 value of earnings, book value of equity, operating cash flow and dividends is 76.4%. The conclusion of this research indicates that there is insufficient evidence that earnings, book value of equity, operating cash flow and dividends have a positive effect on stock prices. Key words: Earnings, Book Value of Equity, Operating Cash Flow, Dividends and Stock Prices